2018
DOI: 10.1021/acs.chemmater.8b03709
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Stability and Photostability of CsPbI3 by Reducing Its Dimensionality

Abstract: Full inorganic perovskites display their poten tial to function as stable photovoltaic materials better than the hybrid organic-inorganic perovskites. However, to date, the cesium lead iodide perovskite, which displays a promising absorbance range, has suffered from low stability, which degrades to a nonactive photovoltaic phase rapidly. ln this work, we show that the black phase of cesium lead iodide can be stabilized when the perovskite dimensionality is reduced. X ray diffraction, absorbance, and scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 29 publications
0
59
0
Order By: Relevance
“…1) 0D quantum dots (QDs): Reducing the crystal size will led to more surface to accommodate organic group, which makes the α-CsPbI 3 more stable. [51] However, the PCE of these devices are below 7%. [48] Xi et al employed with H 2 PbI 4 and assistant doping with Mn 2+ to stabilize the unstable core lattices.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1) 0D quantum dots (QDs): Reducing the crystal size will led to more surface to accommodate organic group, which makes the α-CsPbI 3 more stable. [51] However, the PCE of these devices are below 7%. [48] Xi et al employed with H 2 PbI 4 and assistant doping with Mn 2+ to stabilize the unstable core lattices.…”
mentioning
confidence: 97%
“…[50] Etgar and co-workers also showed when the α-CsPbI 3 dimensionality is reduced, the black phase of α-CsPbI 3 could be stabilized. [51] However, the PCE of these devices are below 7%. 3) Quasi-2D structure: Yuan and co-workers introduced a judicious amount of PEAI and fabricated quasi-2D α-CsPbI 3 .…”
mentioning
confidence: 97%
“…[1][2][3] Tremendous differences in the moisture/light stability and efficiency of all-inorganic perovskites are greatly affected by the halogen I content (or the I/Br ratios). [4][5][6][7][8] Inorganic perovskite with a CsPbIBr 2 formula is considered to be the best option because of its balanced bandgap and stability for potential application in solar cells. [9] In addition, CsP-bIBr 2 perovskite possesses an imperative bandgap of 2.1 eV with a high absorption coefficient in ultraviolet (UV) light region showing a bright-red color, which makes CsPbIBr 2 a promising wide-bandgap component for applications in integrate/tandem solar cells with a UV-filter All-inorganic CsPbIBr 2 perovskite solar cells (pero-SCs) exhibit excellent overall stability, but their power conversion efficiencies (PCEs) are greatly limited by their wide bandgaps.…”
Section: Introductionmentioning
confidence: 99%
“…27 The transition between the phases usually happens due to exposure to air when the a phase, which is cubic, transforms to the b phase (tetragonal structure) and then to the g and d phases (orthorhombic structure). In our previous report, we showed that CsPbI 3 can be stabilized in a two dimensional structure (2D); 28 however, it forms a wide band gap, which makes it problematic to function efficiently in a solar cell. 29 Other methods to stabilize the CsPbI 3 active phase include the addition of different salts such as EuBr 2 , EuCl 2 , and CaI 2 .…”
Section: Introductionmentioning
confidence: 99%
“…29 Other methods to stabilize the CsPbI 3 active phase include the addition of different salts such as EuBr 2 , EuCl 2 , and CaI 2 . [25][26][27][28][29][30][31] Modifying the B site in CsPbI 3 can tune the optical properties and at the same time can enhance its stability. The replacement of lead (Pb) by tin (Sn) in the case of MA + based perovskites leads to a variation in the band gap from 1.55 eV for MAPbI 3 to 1.3 eV for MASnI 3 .…”
Section: Introductionmentioning
confidence: 99%